GAMBARAN KUALITAS PELAYANAN ANTENATAL PADA IBU HAMIL - Kurniati Devi Purnamasari (Journal of Midwifery and Public Health, 2019)
Customer satisfaction will affect customer loyalty, a loyal customer is definitely a satisfied customer. Things like this that encourage organizations or companies develop techniques to increase customer satisfaction in order to reach loyal customers. This research uses a descriptive approach with a population of 98 people. A cross-sectional descriptive study design, consecutive sampling was conducted in June 2015, using a questionnaire. The results showed that the greatest frequency of loyalty was 28 respondents (58%) stated loyal. This shows that patients in the Midwifery Polyclinic of Ciamis Regional Hospital are loyal to antenatal care. This can be seen from every pregnancy examination the patient always visits the hospital.Keywords: Service Quality, Antenatal, Pregnant Women